Efektivitas SPKP2KB Terhadap Tingkat Kesadaran Wajib Pajak Atas Pembayaran Tunggakan Pajak Kendaraan Bermotor Pada Kantor Samsat Cibinong - Wulandari, Yasfini; Andrianto, Toni (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
Optimization of local tax revenue comes from the tax potential that can be explored in that area is no exception the motor vehicle tax. The process of collection and billing through the issuance of tax letter directly hand over to the taxpayer an obligation for the Regional Revenue Agency of West Java Province especially the SAMSAT Office of Bogor Regency in optimizing of motor vehicle tax revenue. The purpose of this study is to determine the effectiveness and contribution of motor vehicle tax collection through the issuance of tax letter, and the motor vehicle tax payment process after the taxpayer receives the tax letter. The final results of this study indicate that the effectiveness of tax letter issuance shows that it has not been effective and the contribution obtained from the disbursement of tax arrears on motor vehicle tax revenue is moderate. Then the motor vehicle tax payment process can be done through service innovations that have been provided by the Regional Revenue Service of West Java Province. Keyword: Effectiveness, motor vehicle taxes, tax revenue, tax letter